Traffic exposures, air pollution and outcomes in pulmonary arterial hypertension: a UK cohort study analysis. Issue 5 (30th May 2019) - Sofianopoulou, Eleni; Kaptoge, Stephen; Gräf, Stefan; Hadinnapola, Charaka; Treacy, Carmen M.; Church, Colin; Coghlan, Gerry; Gibbs, J. Simon R.; Haimel, Matthias; Howard, Luke S.; Johnson, Martin; Kiely, David G.; et al.
While traffic and air pollution exposure is associated with increased mortality in numerous diseases, its association with disease severity and outcomes in pulmonary arterial hypertension (PAH) remains unknown. Exposure to particulate matter with a 50% cut-off aerodynamic diameter ≤2.5 μm (PM2.5 ), nitrogen dioxide (NO2 ) and indirect measures of traffic-related air pollution (distance to main road and length of roads within buffer zones surrounding residential addresses) were estimated for 301 patients with idiopathic/heritable PAH recruited in the UK National Cohort Study of Idiopathic and Heritable PAH. Associations with transplant-free survival and pulmonary haemodynamic severity at baseline were assessed, adjusting for confounding variables defined a priori . Higher estimated exposure to PM2.5 was associated with higher risk of death or lung transplant (unadjusted hazard ratio (HR) 2.68 (95% CI 1.11–6.47) per 3 μg·m −3 ; p=0.028). This association remained similar when adjusted for potential confounding variables (HR 4.38 (95% CI 1.44–13.36) per 3 μg·m −3 ; p=0.009). No associations were found between NO2 exposure or other traffic pollution indicators and transplant-free survival. Conversely, indirect measures of exposure to traffic-related air pollution within the 500–1000 m buffer zones correlated with the European Society of Cardiology/European Respiratory Society risk categories as well as pulmonary haemodynamics at baseline. This association was strongest for pulmonary vascular resistance. In idiopathic/heritable PAH, indirect measures of exposure to traffic-related air pollution were associated with disease severity at baseline, whereas higher PM2.5 exposure may independently predict shorter transplant-free survival. In idiopathic pulmonary arterial hypertension, exposure to indirect measures of traffic-related air pollution was associated with haemodynamic severity and ESC/ERS risk score at baseline, whereas exposure to PM2.5 was associated with long-term prognosis http://ow.ly/G8En30o3swc